Characterizing timber harvest occurrence and intensity to inform forest carbon management across the eastern United States - Matthew B. Russell; Catherine J. Chamberlain; Lynn Riley; Natalia A. Mushegian; John S. Gunn; Ethan P. Belair; Sebastian U. Busby (Frontiers in Forests and Global Change, 2025)
Timber harvesting plays an important role in determining how forest management practices influence carbon storage and sequestration patterns. We analyzed recent harvesting patterns across the eastern United States to quantify harvest area, intensity, and type of silviculture across timberlands. We observed timberland area harvested to vary considerably depending on how harvest occurrence was defined, ranging from 7.8 to 23.4 million hectares harvested between approximately 2016 and 2022. Harvest intensity, as measured by basal area removed in a stand if a harvest occurred, was similar across all ownerships, states, and regions (mean percent of basal area removed was 44.2 ± 29.3% [mean ± standard deviation]), but forest type-level differences were apparent, e.g., harvest intensity was greatest in aspen/birch forests in the Lake States (mean percent of basal area removed of 59.1 ± 31.2%). Policymakers, forest managers, and carbon project developers require an accurate assessment of baseline harvest rates to estimate potential tonnes of additional carbon dioxide equivalents generated in a forest carbon offset project. Using localized timber harvesting patterns derived from historical data will assist in prioritizing the silvicultural prescriptions with the greatest positive climate impacts while additionally informing policies and investments that value the natural capital that forests provide.